2023
DOI: 10.1002/jmv.28824
|View full text |Cite
|
Sign up to set email alerts
|

Corrigendum on “Disease severity and efficacy of homologous vaccination among patients infected with SARS‐CoV‐2 Delta or Omicron VOCs, compared to unvaccinated using main biomarkers”

Abstract: study design, and patients' section of the Materials and Methods.• The phrase "higher symptoms" has been changed to "higher number of symptoms" to reflect the data more accurately in the fourth paragraph of the results and the fifth paragraph of the discussion.• We realized that a reference was missing from the first paragraph of our discussion, so we have added it with the reference. 2• To properly cite our reference and maintain consistency in our discussion section, at the end of the third paragraph of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…CRP is a key pro-in ammatory marker that rises dramatically in severe COVID-19 patients and falls as the patient heals [38][39][40][41]. The use of CCOGA decreased the CRP level in the treatment arm as compared to the control arm.…”
Section: Discussionmentioning
confidence: 99%
“…CRP is a key pro-in ammatory marker that rises dramatically in severe COVID-19 patients and falls as the patient heals [38][39][40][41]. The use of CCOGA decreased the CRP level in the treatment arm as compared to the control arm.…”
Section: Discussionmentioning
confidence: 99%
“…This approach aims to enhance and prolong immunity against the virus, taking into account the dynamic nature of the pandemic and the need for long-term protection [10]. P zer-BioNTech's COVID-19 vaccine is an actual ght against the pandemic, concerning the e cacy and severity of homologous vaccination, it was found that those infected with SARS-COV-2 who had been vaccinated with double doses (fully vaccinated) of vaccines had a lower risk of hospitalization, emphasizing the importance of the booster doses launch [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 persistently extended its global reach, giving rise to mutations and distinct clades and reinfection [2,3], while impacting various organs in the human body [4,5]. While vaccines have proven to be effective tools in controlling the spread of the virus and preventing severe illness and death, a concerning trend emerged [6,7]. Consequently, reports indicated vaccine hesitancy within speci c demographic groups.…”
Section: Introductionmentioning
confidence: 99%